2021
DOI: 10.3390/horticulturae7070180
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Salinity and LED Lights on the Yield and Quality of Purslane (Portulaca oleracea L.) Microgreens

Abstract: The present work aims to explore the potential to improve quality of purslane microgreens by combining water salinity and LED lighting during their cultivation. Purslane plants were grown in a growth chamber with light insulated compartments, under different lighting sources on a 16 h d−1 photoperiod—fluorescent lamps (FL) and two LED treatments, including a red and blue (RB)) spectrum and a red, blue and far red (RB+IR) LED lights spectrum—while providing all of them a light intensity of 150 µmol m−2 s−1. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 77 publications
3
29
0
Order By: Relevance
“…Brassica carinata microgreens produced greater amounts of phenolics when treated with monochromatic blue compared to red and 50% red/ 50% blue light [29]. As with the green basil used in this study, Lobiuc et al [42] found a higher phenolic content in green basil (Ocimum basilicum) under increased red light portion, while Gimenez et al [40] reported greater total phenolic content in purslane microgreens treated with red-blue light compared to fluorescence and red-blue, including far-red. Romaine baby leaf lettuce had significantly higher phenol, but lower anthocyanin, and tocopherol amounts under supplemental light with a peak at 622 nm, and less ascorbic acid and tocopherols under supplemental light, with a peak at 595 nm [43].…”
Section: Phytochemical Analysesmentioning
confidence: 54%
See 2 more Smart Citations
“…Brassica carinata microgreens produced greater amounts of phenolics when treated with monochromatic blue compared to red and 50% red/ 50% blue light [29]. As with the green basil used in this study, Lobiuc et al [42] found a higher phenolic content in green basil (Ocimum basilicum) under increased red light portion, while Gimenez et al [40] reported greater total phenolic content in purslane microgreens treated with red-blue light compared to fluorescence and red-blue, including far-red. Romaine baby leaf lettuce had significantly higher phenol, but lower anthocyanin, and tocopherol amounts under supplemental light with a peak at 622 nm, and less ascorbic acid and tocopherols under supplemental light, with a peak at 595 nm [43].…”
Section: Phytochemical Analysesmentioning
confidence: 54%
“…On the contrary, Pennisi et al [30] reported significantly greater antioxidant capacity (ferric reducing antioxidant power: FRAP) in basil plants treated with a red/blue ratio of 2 units compared to those treated with 0.5 or 1, while total flavonoid concentration was promoted under a red/blue ratio of 3 units compared to ratios ranging from 0.5 to 4 units. In a study with purslane (Portulaca oleracea) microgreens, antioxidant capacity was not affected by fluorescent, red-blue, or red-blue, including far-red lights [40].…”
Section: Phytochemical Analysesmentioning
confidence: 94%
See 1 more Smart Citation
“…Zheng and Van Labeke [34] reported that total phenol content in the leaves of Dendranthema morifolium was suppressed under B light, although this effect depended on the cultivar. B, R, and FR wavelengths also regulate the biosynthesis of phenol contents in a direct or indirect manner through signaling, which leads to the expression of key enzymes, or through upregulating the production of shikimic acid, which is a precursor of phenol contents [35]. Moreover, the activity of phenylalanine ammonia lyase (PAL), a major enzyme involved in phenolic biosynthesis, is known to be regulated by light quality [36].…”
Section: Antioxidantmentioning
confidence: 99%
“…The application of UV-B, alone or in combination with UV-C, has not been widely studied as a revalorization tool for maintaining and/or increasing the main key compounds in F&V by-products [ 69 ]. Although light-emitting diodes (LEDs) are increasingly adopted for the production of several vegetable modalities and for quality preservation during storage [ 70 ], influencing the metabolic pathways (biosynthesis of several bioactive compounds) [ 71 , 72 , 73 ]. No published information is already available concerning the effect of this light stress in F&V by-products.…”
Section: Potential and Innovative Non-thermal Techniques For Revalorization Of Fruit And Vegetables By-productsmentioning
confidence: 99%